CHARACTER EXAMINATION IN ANTON CHEKHOV'S FAT AND THIN - Agnes Tianingsih; Dinda Salsabila; Roida Febrianti (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
This study aims to explore the impact of societal hierarchies on personal relationships and behavior through the characters in Anton Chekhov's "Fat and Thin". The objective is to understand the psychological mechanisms and societal influences that drive character transformations upon the revelation of social status differences. Using qualitative analysis, the research examines the interactions between the characters Fat (Mischa) and Thin (Porfiry), focusing on the sudden shift in Thin's behavior from informal camaraderie to formal subservience once Fat's higher rank is revealed. The methodology involves a close reading of the text, applying psychological theories such as cognitive dissonance and Heider’s Balance Theory, and societal conditioning frameworks to dissect Thin's behavioral change. The results indicate that Thin's immediate deference is a defense mechanism triggered by internal psychological discomfort and societal expectations. This shift illustrates the profound influence of hierarchical structures on personal behavior and relationships. The study concludes that Chekhov critiques the superficial respect accorded to authority over genuine human connection, reflecting on the absurdityd and superficiality of societal norms. Key findings highlight the interplay between psychological discomfort, societal conditioning, and defense mechanisms in shaping individual behavior